Prevalence and risk factors for hepatitis C virus in Beta thalassemic patients attending blood diseases center in Ibn- AL -Baladi Hospital, Baghdad - Zena Hussain Ali (مجله كليه طب الكندي, 2018)
Background: Thalassemias are a group of heterogeneous genetic disorders, in which the rate of production of hemoglobin is partially or completely suppressed due to reduced rate of synthesis of α or β- chain